Small woodlands and butterfly conservation on farmland - Feber, R; Johnson, P; Manley, W; Macdonald, D (Association of Applied Biologists, 2018)
The impacts of small woodlands on farmland biodiversity are less well studied than those of other habitats, such as hedgerows and field margins. Butterfly abundance and species richness were recorded along transects on two farms in southern England, one organic and one conventional, which had small woodlands. Woodland edges were particularly important for two species: comma Polygonia c-album and speckled wood Parare aegeria. Both were more abundant on woodland edges compared to hedgerows or field margins. A range of declining wider countryside species, including gatekeeper Pyronia tithonus and meadow brown Maniola jurtina, also frequented woodland edges. The quality of woodland edges was influential. Butterfly abundance was higher on woodland edges with a shrub layer. There was some evidence that bramble presence had a greater effect on butterfly abundance on the conventional compared to the organic farm. Small woodlands can make an important contribution to biodiversity conservation on farmland.